The Effect of Lithium on Inflammation-Associated Genes in Lipopolysaccharide-Activated Raw 264.7 Macrophages - Raymond T. Makola; Vusi G. Mbazima; Matlou P. Mokgotho; Vincent S. Gallicchio; Thabe M. Matsebatlela (Hindawi Limited, 2020)
Lithium remains the preferred Food and Drug Administration- (FDA-) approved psychiatric drug for treatment of bipolar disorders since its medical establishment more than half a century ago. Recent studies revealed a promising role for lithium in the regulation of inflammation, oxidative stress, and neurodegeneration albeit unclear about its exact mode of action. Thus, the intention of this study is to delineate the regulatory mechanisms of lithium on oxidative stress in lipopolysaccharide- (LPS-) activated macrophages by evaluating its effects on nuclear factor-κB (NF-κB) activity and mRNA expression of multiple oxidative stress-related NF-κB genes. Raw 264.7 macrophages were treated with up to 10 mM lithium, and no change in cell proliferation, viability, growth, and cell adhesion was observed in real time. Pretreatment with low doses of lithium was shown to reduce nitric oxide (NO) production in LPS-activated macrophages. A reduced internal H2DCFDA fluorescence intensity, indicative of reduced reactive oxygen species (ROS) production, was observed in LPS-activated Raw 264.7 macrophages treated with lithium. Lithium has been shown to lower the production of the chemokine RANTES; furthermore, this inhibitory action of lithium has been suggested to be independent of glycogen synthase kinase-3 β (GSK3β) activity. It is shown here that lithium modulates the expression of several inflammatory genes including IκB-α, TRAF3, Tollip, and NF-κB1/p50 which are regulators of the NF-κB pathway. Moreover, lithium inhibits NF-κB activity by lowering nuclear translocation of NF-κB in LPS-activated macrophages. This is the first study to associate Tollip, Traf-3, and IκB-α mRNA expression with lithium effect on NF-κB activity in LPS-activated Raw 264.7 macrophages. Although these effects were obtained using extratherapeutic concentrations of lithium, results of this study provide useful information towards understanding the mode of action of lithium. This study associates lithium with reduced oxidative stress in LPS-activated Raw 264.7 macrophages and further suggests candidate molecular targets for the regulation of oxidative stress-related diseases using lithium beyond bipolar disorders.